Notes respecting the recent Excavations at Cambuskenneth Abbey (Proceedings of the Society of Antiquaries of Scotland, 1865)
A notice of excavations taking place at Cambuskenneth Abbey near Stirling on the advice of members of the Society.Meeting notes for 13 June, 1864 are appended.